HOW TO IMPROVE THE ENTREPRENEURIAL MOTIVATION THROUGH ENTREPRENEURIAL INTENTION, ATTITUDES, AND ENVIRONMENTAL ASPECTS - Pravitasari, Chairani Fadhila; Purnomo, Widhiatmoko Herry; Ramadhan, Muhammad Syah Fibrika; Widiastuti, Ekaningtyas (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
Students who enter the world of entrepreneurship show extraordinary enthusiasm and initiative in developing their own businesses. They do not only focus on academic studies, but also actively seek opportunities and are ready to take risks to build independent businesses. The focus of this study is to understand how entrepreneurial motivation among students can be improved through entrepreneurial intentions, attitudes, and environmental factors. Data were collected through questionnaires, with convenience sampling techniques, and analyzed using Multiple Regression in the SPSS program. A total of 84 respondents were involved in this study. The results show that Entrepreneurial Intention and Attitude has a positive influence on entrepreneurial motivation. However, the results of other hypothesis tests revealed that Knowledge of Available Entrepreneurial Support and Perceived Barriers to Starting a Business did not affect entrepreneurial motivation. Overall, this study emphasizes the importance of strengthening entrepreneurial intentions as a key factor in encouraging entrepreneurial motivation among students.